Advances in resources, biosynthesis pathway, bioavailability, bioactivity, and pharmacology of ochnaflavone - Shiye Lin; Abirami Ramu Ganesan; Celia Vargas‐De‐La‐Cruz; Jaime Ortiz‐Viedma; Jianbo Xiao (Future Postharvest and Food)
Abstract Ochnaflavone is a naturally occurring biflavonoid mainly isolated from Ochna integerrima, manifests health benefits encompassing antidiabetic, anticancer, anti‐cardiovascular, and anti‐inflammatory activities. However, most bioactivity research has focused on in vitro experiments, rather than in vivo disease models, toxicological assessments, and human clinical trials. Moreover, a comprehensive review of the pharmacological aspects of ochnaflavone is conspicuously lacking. Thus, this review provides a concise and comprehensive summary of existing knowledge on the chemical structure, plant origin, physical properties, biotransformations, and multifaceted biological activities of ochnaflavone along with an in‐depth exploration of the complex molecular mechanisms behind these activities, including signaling pathways and gene expression regulation, with the aim of promoting future theoretical needs for ochnaflavone in clinical trials and providing comprehensive insights into the research and application of this valuable natural compound.